2019
DOI: 10.1093/dote/doz067
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity following salvage esophagectomy for squamous cell carcinoma: the MD Anderson experience

Abstract: SUMMARY The survival advantage associated with the addition of surgical therapy in esophageal squamous cell carcinoma (ESCC) patients who demonstrate a complete clinical response to chemoradiotherapy is unclear, and many institutions have adopted an organ-preserving strategy of selective surgery in this population. We sought to characterize our institutional experience of salvage esophagectomy (for failure of definitive bimodality therapy) and planned esophagectomy (as a component of trimodality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 20 publications
1
60
0
Order By: Relevance
“…ER, including ESD, is generally indicated for lesions within T1a in depth without ulceration or severe fibrosis; therefore, the indication of ER is limited and must be judged based on the operator's skill. While salvage surgery is the most invasive treatment method for patients with local failure after CRT for esophageal cancer, it can be a curative intent treatment when complete resection is achieved without any fetal complications [20,21]. Therefore, a patient's physical tolerability for surgery should be discussed with surgeons at the conference, presenting the advantages and disadvantages of salvage surgery for patients.…”
Section: Indication Of Pdt For Local Failure After Radiotherapy For Esophageal Cancermentioning
confidence: 99%
“…ER, including ESD, is generally indicated for lesions within T1a in depth without ulceration or severe fibrosis; therefore, the indication of ER is limited and must be judged based on the operator's skill. While salvage surgery is the most invasive treatment method for patients with local failure after CRT for esophageal cancer, it can be a curative intent treatment when complete resection is achieved without any fetal complications [20,21]. Therefore, a patient's physical tolerability for surgery should be discussed with surgeons at the conference, presenting the advantages and disadvantages of salvage surgery for patients.…”
Section: Indication Of Pdt For Local Failure After Radiotherapy For Esophageal Cancermentioning
confidence: 99%
“…47 R0 resection was performed in 42.4%-86.9% of cases. [18][19][20][21][22][23][24][25][26][27][28][29][33][34][35][36][37][38][39][40][41]44,46 One-year, 3-year, and 5-year OS rates were 45.7%-84%, 18,27,34,[36][37][38]40,46 29.8%-63%, 18,[26][27][28]34,38,40,46 and 5.7%-51.6%, 18,26,27,[34][35][36][37]46 respectively. Multivariate analysis revealed the following independent prognostic factors: R0 resection, 21,[23][24]…”
Section: Ta B L E 1 Summary Of Studies On Esophagectomy After Dcrtmentioning
confidence: 99%
“…However, in the JCOG0502 trial, salvage esophagectomy was performed in 21 of 159 patients (13.2%) in the chemoradiation group, and it should be noted that morbidity following salvage esophagectomy is high. A retrospective review from our institution showed that major postoperative complications after salvage esophagectomy frequently occurred in 71.4% 62 . The JCOG1406-A trial compared two Japanese trials conducted in the same era: JCOG9906, which evaluated definitive chemoradiation, and JCOG9907, which evaluated preoperative chemotherapy followed by esophagectomy for clinical stage II/III ESCC 63 .…”
Section: Future Perspectivementioning
confidence: 99%